The works : anatomy of a city - Marech, Wendy (New York : Penguin Press, 2005)
Moving people : streets, subway, bridges & tunnels ##Moving freight : rail freight, maritime freight, air cargo, markets ##Power : electricity, natural gas, steam ##Communications : telephone, moving the mail, the airwaves ##Keeping it clean : water, sewage, garbage ##The future.
boek